2001
DOI: 10.1038/sj.cgt.7700333
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated interferon-β gene therapy suppresses growth and metastasis of human prostate cancer in nude mice

Abstract: The purpose of this study was to determine the effects of interferon -(IFN -) gene transfer on the growth of PC3MM2 human prostate cancer cells in nude mice. Intralesional delivery of an adenoviral vector encoding murine IFN -( AdIFN -) , but not a vector encoding bacterial -galactosidase ( AdLacZ ) , suppressed PC3MM2 tumors in a dose -dependent manner. At the highest dose ( 2Â10 9 plaque -forming units, PFU ) , a single injection of AdIFN -( but not AdLacZ ) suppressed orthotopic PC3MM2 tumors and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 45 publications
(32 reference statements)
2
43
0
4
Order By: Relevance
“…There is a large body of evidence that generation of NO, mediated by inducible NOS, can have cytotoxic effects on neoplastic cells and inhibit their potential for growth in vivo. [15][16][17][18][19][20][21][22][23][24] In addition to this mechanism, which generates NO throughout a sustained period of time, 24 we have shown here that tumor cell arrest can trigger the immediate release of NO via eNOS-dependent mechanisms and subsequently trigger apoptosis in these cells. Previous experiments in the liver have inferred a role for eNOS as an effector of B16 melanoma cytotoxicity on the basis that NO release occurred immediately (Ͻ5 minutes) after tumor cell arrest in the hepatic sinusoid.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence that generation of NO, mediated by inducible NOS, can have cytotoxic effects on neoplastic cells and inhibit their potential for growth in vivo. [15][16][17][18][19][20][21][22][23][24] In addition to this mechanism, which generates NO throughout a sustained period of time, 24 we have shown here that tumor cell arrest can trigger the immediate release of NO via eNOS-dependent mechanisms and subsequently trigger apoptosis in these cells. Previous experiments in the liver have inferred a role for eNOS as an effector of B16 melanoma cytotoxicity on the basis that NO release occurred immediately (Ͻ5 minutes) after tumor cell arrest in the hepatic sinusoid.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44][45][46][47] The mechanism of action is complex as type I interferons induce a pleiotropic array of responses, including direct inhibition of growth of various tumors cells and modulation of host immune cells such as natural killer (NK) cells, 35,39,41,43,44,46 polymorphonuclear (PMN) cells, 43 macrophages, 36,39,41,47 CD4( þ ) 41,43 and CD8( þ ) 36,[41][42][43] cells. In most studies, as we observed in the experiments reported herein, local adenovirus mediated IFNb gene therapy was preferred over systemic due to increased local transgene concentrations and reduced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional delivery of IFNb by adenovirus have been shown to reduce tumors by a direct antitumor effect 36,40,41,45 and through activation of innate and adaptive immune responses. 36,37,40,41,47 On the other hand, systemic delivery of Ad-IFNb resulted in efficient hepatocyte transduction with the vector and potent liver metastases inhibition. 35,46 An interesting distinction between the two type I IFNs is the relative essential role for the effect of IFNb on stimulation of immune cells as there was a loss of efficacy in tumor bearing SCID-BEIGE.…”
Section: Discussionmentioning
confidence: 99%
“…36 Targeting PC by molecular abnormality remains elusive because of the accumulation of multiple genetic changes during its multistep carcinogenesis. During the last decade, numerous studies illustrated the gene transfer or systemic delivery of IFN-b to inhibit tumor growth in multiple animal models from gliomas, 37 to hepatocellular carcinoma, 38 metastatic breast cancer, 39 prostate cancer, [40][41][42] rectum, colon and endometrial tumors, [43][44][45] lung tumors, 46,47 renal cell carcinomas and melanoma, 48,49 neuroblastoma, 50,51 disseminated peritoneal cancer, 52 bladder cancer, 53 malignant mesothelia 54 and fibrosarcomas. 55 Recently, a cancer gene therapy trial for gliomas based on the intratumoral administration of IFN-b) was shown to be feasible and associated with apoptosis induction.…”
Section: Lentiviral Vectors For Pc Therapy E Ravet Et Almentioning
confidence: 99%